Practical management of the increasing burden of non-alcoholic fatty liver disease. Issue 3 (23rd September 2010) - Mouralidarane, Angelina; Lin, Ching-I; Suleyman, Narin; Soeda, Junpei; Oben, Jude A
Abstract : Obesity-induced liver disease (non-alcoholic fatty liver disease (NAFLD)) describes a spectrum from steatosis through steatohepatitis to cirrhosis. Its prevalence is rising in tandem with societal rates of obesity which through consequent insulin resistance and fat deposition in hepatocytes lead to hepatocyte death and attempts at repair, which if persistent, lead to activation of liver fibrogenic cells. NAFLD, which may also progress to primary liver cancer, is now the most common cause of chronic liver disease in affluent countries. There is currently no single accurate diagnostic test besides a liver biopsy. The decision to consider a liver biopsy will be informed by the presence of insulin resistance determined by comparatively easy-to-measure factors together with other putative markers of progression such as hypertension. If a liver biopsy is performed, patients with steatosis with no evidence of inflammation may be less aggressively managed while those with steatohepatitis, since they have a faster trajectory to cirrhosis, should be managed more robustly. Besides lifestyle changes and increased aerobic exercise other strategies include considering referral to centres with ongoing clinical trials. Emerging treatments include α1 adrenoceptors antagonists, angiotensin receptor blockers, glitazones and vitamin E.